PERSEPSI PENDENGAR TERHADAP PROGRAM REVIEW KELAKUAN TEMAN ATAU TETANGGA RADIO EBS FM DENGAN TOPIK PERMASALAHAN UANG DAN HUTANG (Universitas Negeri Surabaya, 2023)
This study aims to determine the perception of EBS FM Radio listeners on social problems of money and debt in the Review of Behavior of Friends or Neighbors program based on differences in background, experience, socio-culture, age, and work of informants. The Friends or Neighbors Behavior Review Program is made according to the